Fabrication of a white electroluminescent device based on bilayered yellow and blue quantum dots1. Issue 12 (28th March 2015) - Kim, Jong-Hoon; Lee, Ki-Heon; Kang, Hee-Don; Park, Byoungnam; Hwang, Jun Yeon; Jang, Ho Seong; Do, Young Rag; Yang, Heesun
<x xml:space="preserve">Abstract</x> A bicolored white quantum dot-light-emitting diode has been demonstrated using a unique QD combination of blue CdZnS/ZnS and yellow Cu–In–S/ZnS.